SISTEM INFORMASI PERTANGGUNG JAWABAN SURAT PERINTAH PERJALANAN DINAS (SPPD) BERBASIS WEB APPLICATION PADA DINAS PARIWISATA, PEMUDA DAN OLAHRAGA - Nurfadillah P; Husni Sulaiman; Sri Asfirawati Halik (CV. LAJAGOE PUSTAKA, 2025)
Th This study aims : (1) Design an Information System for Official Travel Warrant Coverage (SPPD) on the Tourism, Youth and Sports Office Web Application. (2) To implement an Information System for accountability for official travel orders (SPPD) at the Web Application-based Tourism, Youth and Sports Office. This study uses the waterfall method. This method consists of 6 stages including Requirements Analysis, Design, Program Code Writing, Testing, Implementation, and Maintenance. This research uses UML (Unified Modeling Language) design which consists of Use Case Diagrams, Class Diagrams, Activity Diagrams and Sequence Diagrams. Information System for Official Travel Orders (SPPD) at the Tourism, Youth and Sports Office of Bulukumba Regency based on Web Applications that can be used on computers and laptops by opening the link provided. This system can be run based on the system work procedures that the user wants, making it easier in the process of making official orders, fast work systems without having to take a lot of time to process. This system also provides a place to store data for business travel orders that have been made previously so that there is no need to open and search for data in stacks of documents because this system is made to manage files in a structured manner without the need to fear that the paper will be damaged or lost.